Insectivore Plants Nepenthes sp. at Mount Merbabu - HERY MULYANTO; DEWI CAHYUNINGDARI; AHMAD DWI SETYAWAN (Society for Indonesian Biodiversity, 2000)
The aims of the research were to know the existence of the Nepenthes at mount Merbabu, variations of its morphology, associated plants, and ecological conditions. Nepenthes are one of plants that were categorized as conserved plant by Indonesian government as indicated in PPRI No. 7/1999. Many researchers attracted to study this unique plant since itâ€™s distinct feature and the way to get nutrient by trapping insects at its sac. Samples were taken randomly along the path for climbing from Selo, Boyolali to the top of the mountain between April to May 2000. The results show that the plants were found at the altitude of around 1500 to 2000 tsl. There were two forms of the sacs, long and short at the same individual plants. The plants grow coiling on Myristica trees and shrubs of Thunbergia fragrans Roxb., and also could grow at the stoned-soil.Â© 2000 Jurusan Biologi FMIPA UNS SurakartaKey words: Nepenthes, morphology, ecology